Triptycene-Based and Amine-Linked Nanoporous Networks for Efficient CO2 Capture and Separation - Alam, Akhtar; Bera, Ranajit; Ansari, Mosim; Hassan, Atikur; Das, Neeladri (Frontiers in Energy Research, 2019)
A set of five nanoporous (pore size <100 nm) amine-functionalized and triptycene-based organic polymers (TBPALs) were prepared using commercially available phenols (such as quinol and phloroglucinol) and triptycene amines. C–N bonds were formed in the polymerization reactions without employing transitional metal catalysts such as PdII or CuI. TBPALs demonstrated their ability to reversibly capture small gas molecules such as CO2, H2, CH4, and H2. Highest uptake of CO2 and H2 was observed for TBPAL2 at 163.7 mg g−1 (273 K) and 16.2 mg g−1 (77 K), respectively.